The Influence of Age, Gender, Income Level and Tax Sanctions on Taxpayer Compliance among MSMEs in Wonogiri Regency - Lamuda, Dido Bernata Citra; Nursiam, N (Universitas Muhammadiyah Surakarta, 2024)
Purpose: One sector that plays an important role in tax revenue is Micro, Small, and Medium Enterprises (MSMEs). MSMEs are increasingly demonstrating their role in the country's economic growth. However, taxes are still seen as a burden to be avoided by MSMEs at all costs. Not all taxpayers are aware of their obligations to pay taxes. This can lead to a mindset and behavior of tax noncompliance, potentially resulting in tax evasion by providing incorrect income reports. This study aims to examine the effects of age, gender, income level, and tax sanctions on tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Wonogiri Regency. Methodology: This is a quantitative research. The population of this study consists of MSME operators in Wonogiri Regency who are registered with the Office of Cooperatives, Small and Medium Enterprises, and Industry and Trade of Wonogiri Regency. The sampling method used in this study is non-probability sampling, specifically convenience sampling. According to calculations using the Slovin formula, a sample size of 100 was obtained. The data analysis methods used in this study include data quality tests, such as validity and reliability tests, classical assumption tests, including normality test, multicollinearity test, and heteroscedasticity test, and hypothesis testing, including multiple linear regression test, partial test (t-test), model feasibility test (F-test), and coefficient of determination test (R²) using SPSS software. Results: This study reveals that Income Level and Tax Sanction variables have a significant effect on Taxpayer Compliance. Meanwhile, the age and gender variables has no effect on taxpayer compliance. Applications/Originality/Value: This study analyzes the influence of age, gender, income level, and tax sanctions on tax compliance among MSMEs, which can be used by policymakers to develop more effective programs for increasing tax compliance. The results of this study can be applied in formulating tax policies that consider the demographic characteristics of taxpayers. The originality of this research lies in the integration of demographic variables with aspects of tax sanctions, providing new insights into the factors influencing compliance. The value of this study is its contribution to understanding the dynamics of tax compliance in MSMEs, which is essential for increasing national revenue and the sustainability of the MSME sector.